REPRESENTASI NILAI MORAL DALAM CERITA RAKYAT KAILI DI KABUPATEN DONGGALA - Himawan, Romi; Lembah, Gazali; Ulinsa, Ulinsa (BAHASANTODEA, 2017)
The research problems were (1) What moral value is contained on Kailinese folklore in Donggala district? (2) What is the representation of moral value on Kailinese folklore in Donggala district? The objectives of this research are (1) to describe the moral value on Kailinese folklore in Donggala, and (2) to describe the representation of moral value on Kailinese folklore in Donggala district. The research type was qualitative research. Data were collected through direct observation, recording, interview, note and document analysis. Data analysis used the techniques of Miles and Huberman. The results of this research show that moral values that exist on Kailinese folklore in Donggala district namely individual, social, religious. The results of representation of moral values that are never give up, strong, happy, honest, obedient, curiosity, trusteeship, democratic, loving pet, affection, helping parents, alert, respecting parents, helping, helpful, friendly believe in the power of God and pray.